90.5k views
3 votes
8(-5x + 3) use x = 6 how do i do this​

2 Answers

4 votes

Answer:

-216

Explanation:

  1. Plug the value of x (6) in: 8(-5 × 6 + 3)
  2. -5 × 6 = -30
  3. Plug -30 in: 8(-30 + 3)
  4. -30 + 3 = -27
  5. Plug -27 in: 8(-27)
  6. 8 × -27 = -216
User Mark Buikema
by
4.7k points
3 votes

Answer:

-216.

Explanation:

So we have the equation:


8(-5x+3)

And we want to evaluate it at x=6.

So, substitute 6 for x:


=8(-5(6)+3)

Multiply:


=8(-30+3)

Add:


=8(-27)

Multiply again:


=-216

And we're done!

Our answer is -216.

User Rishil Patel
by
5.0k points